STUDI EKSPERIMENTAL KUAT TEKAN MORTAR EPOXY DENGAN KOMPOSISI CAMPURAN SENDIRI SEBAGAI MATERIAL PERBAIKAN BETON - BONAVENTURA HARYANTO UMBU TAY; Faras Y. Alfarisy; Ryan Iskandar; Alvin Alfredo Bara (Racic : Rab Construction Research, 2026)
This study aims to evaluate the compressive strength performance of custom-mixed epoxy mortar as an alternative concrete repair material, compared to the ready-mix Sikafloor-81 Epocem. The epoxy mortar was composed of epoxy resin, cornice adhesive, and silica sand, with three epoxy ratios: 0.5, 0.7, and 1.0 by weight of cornice. Compressive strength tests were conducted at 7, 14, and 28 days. Results showed that RE 0.7 and RE 1.0 variants exceeded the 45 MPa target at 28 days, with the highest value reaching 53.80 MPa. In contrast, the Sikafloor-81 Epocem exhibited strength reduction over time. ANOVA confirmed statistically significant differences among the variants. Therefore, the custom epoxy mortar proved superior and feasible to be developed as a reliable solution for concrete repair applications